Penginversian Kalimat Pada Teks Prosedur Sebagai Pengembangan Bahan Ajar Inovatif Di Sekolah Menengah Pertama - Murni Lestari, Betty; , Drs. Agus Budi Wahyudi, M.Hum (2017)
This study aims to find out the form of inversion sentences in the text of the procedure, describe the function of the conversion of sentences in the text of the procedure, and to know the development of innovative teaching materials of the text of the procedures in Junior High School. This research uses descriptive qualitative research type. Data collection techniques used in this study is the technique of documentation and techniques refer to. The validity of data in this study using triangulation theory. Data analysis in this research is done with method of agih and padan. The basic technique used is the technique of determining element (PUP) and technique for the direct element (BUL). The advanced techniques are reverse engineering and extension techniques. The inverse sentence in the text of the procedure there are 4 kinds, namely: declarative inversion sentence, imperative inversion sentence, interrogative inversion sentence and interjectional inversion sentence. The sentence-clicking function in the text of the procedure is used for focusing, which is to highlight the constituents in the focus of the sentence. The development of teaching materials in this study resulted in handouts in accordance with core competence 3.6 and basic competencies 4.6 class VII Junior High School.